Amino‐methyl coumarin as a potential SERS@Ag probe for the evaluation of protease activity and inhibition. (3rd August 2016) - Soualmia, Feryel; Touhar, Si Ammar; Guo, Liangfeng; Xu, Qisong; V. Garland, Marc; Colomban, Philippe; Percot, Aline; El Amri, Chahrazade
Abstract : Proteases are found deregulated in many diseases including cancer and neurodegenerative diseases. They thus represent good therapeutical targets for the development of inhibitors mainly small organic molecules. Peptide substrates containing fluorogenic groups constitute central tools for the monitoring of protease activities and inhibitor screening platforms. Amino‐methyl coumarin (AMC) is a well‐known fluorogenic group that functionalized a huge number of peptide substrates used for kinetics in vitro but also in vivo . However, either autofluorescence or quenching of the AMC fluorescence could compromise selection and accurate evaluation of these inhibitors. It is thus needed to explore alternative spectroscopic tools to unravel these limitations. Here, we investigate whether AMC could constitute a valuable Surface Enhanced Raman Spectroscopy probe in the presence of Creighton' silver colloids under 532‐nm excitation to monitor protease activity and to evaluate inhibitors. The kallikrein‐related peptidase 8 was used as model of proteolytic enzyme. Band‐Target Entropy Minimization analysis was successfully used to validate the present Surface Enhanced Raman Spectroscopy approach. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Peptide substrates containing fluorogenic groups are central tools for the monitoring of protease activities and inhibitors screening platforms. Amino‐methyl coumarin (AMC) is a well‐known fluorogenic group that functionalized a large number of peptide substrates used for kinetics in vitro but also in vivo . Here, we investigate whether AMC could constitute a quantitative SERS probe in the presence of Creighton silver colloids under 532‐nm excitation to monitor protease activity and evaluate inhibition mechanisms. SERS@Ag constitutes a promising tool to follow changes within inhibitory molecules during their interactions with target enzyme.